Movie recommendation system / Najwa Syamimie Hasnu - Hasnu, Najwa Syamimie (2020)
Movie Recommendation System is essentially developed for the purpose of producing a movie recommendation list therefore, it is paired with algorithm to provide the desired functionalities and features in the system. As known, users prefer to use system that recommend suitable items according to their preferences so that they will not have to go through hundreds of movie list to find something that they may like. It was difficult enough to look for list of movies on the Internet, moreover to browse through the long list to find what they have been looking for. Therefore, it is essentially needed for the user to use a recommendation system that can help them get through with this process. As a result, the objectives for this project are to study the most suitable algorithms used for a movie recommender system, to implement Collaborative Filtering algorithm on a movie recommender system prototype and to test the functionality of the movie recommender system, hi this project, a movie recommendation system with the use of Collaborative Filtering is proposed to produce a set list of movies for the users. This process will be done with the process of calculation the similarity of the movies rated by the users and a recommendation list will be produced through it. PHPMyAdmin is used to store the dataset and also acts as a database for user information. The algorithm chosen was implemented using Java Programming language and was tested using Root Means Square Error (RMSE) formula.